Pyridazine (1, 2-diazine): A Versatile Pharmacophore Known for its Utility in Biological Systems - Sharma, Swati (Current Bioactive Compounds, 2024)
The present review describes the biological essence of pyridazine scaffold. Around 142 biologically potential pyridazine entities are gathered in a pile from documented literature. Some of them are commercially available drugs, few are naturally occurring pyridazine compounds, and a wide variety of compounds containing pyridazine moiety are biologically tested, and some are under clinical trials. Rather than collecting large quantities of data, an attempt is made to compile valuable entities. However, efforts have been made to compile the maximum literature in brief. The main motto of this review is to provide a combination of therapeutically active pyridazine containing compounds for further drug design, discovery, and development to contribute to future medicinal chemistry. Our approach is to bring the most biologically potent pyridazine derivatives to medicinal chemists, biologists, pharmacists, and organic chemists. The present work encompasses the literature from 2000-2022 from different and authentic sources. The work is divided according to the bioactive nature of pyridazine nucleus.
Keywords: molecular docking